Swiss Interdisciplinary Management Programme for Heart Failure (SWIM-HF) (Swiss Medical Weekly, 2011)
PRINCIPLES: International guidelines for heart failure (HF) care recommend the implementation of inter-professional disease management programmes. To date, no such programme has been tested in Switzerland. The aim of this randomised controlled trial (RCT) was to test the effect on hospitalisation, mortality and quality of life of an adult ambulatory disease management programme for patients with HF in Switzerland. METHODS:Consecutive patients admitted to internal medicine in a Swiss university hospital were screened for decompensated HF. A total of 42 eligible patients were randomised to an intervention (n = 22) or usual care group (n = 20). Medical treatment was optimised and lifestyle recommendations were given to all patients. Intervention patients additionally received a home visit by a HF-nurse, followed by 17 telephone calls of decreasing frequency over 12 months, focusing on self-care. Calls from the HF nurse to primary care physicians communicated health concerns and identified goals of care. Data were collected at baseline, 3, 6, 9 and 12 months. Mixed regression analysis (quality of life) was used. Outcome assessment was conducted by researchers blinded to group assignment. RESULTS:After 12 months, 22 (52%) patients had an all-cause re-admission or died. Only 3 patients were hospitalised with HF decompensation. No significant effect of the intervention was found on HF related to quality of life. CONCLUSIONS:An inter-professional disease management programme is possible in the Swiss healthcare setting but effects on outcomes need to be confirmed in larger studies.